2002
DOI: 10.1515/jpem.2002.15.5.589
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ultrasensitive LH Assay: A Useful Tool in the Early Diagnosis of Male Pubertal Delay?

Abstract: The aim of this study was to evaluate the usefulness of basal measurements of gonadotropins in distinguishing between constitutionally delayed puberty (DP) and hypogonadotropic hypogonadism (HH), comparing its diagnostic efficiency with that of the dynamic GnRH infusion test (0.83 microg/min during 120 min). We studied 20 males, chronological age (CA) 14-18 years, with a final diagnosis of DP (n = 8), partial HH (n = 5) and complete HH (n = 7), confirmed by follow-up. We also evaluated basal samples of ultrase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…[7][8][9][10] Pharmacological stimulation of gonadotropins by GnRH also showed overlapping gonadotropin serum concentrations. 7,10,11 In contrast, pharmacological stimulation of gonadotropins by GnRH agonists (GnRHa) showed a significantly higher discriminatory potential. GnRH agonists have longer half-lives than GnRH and a stronger affinity for the GnRH receptor, causing a supraphysiological and sustained stimulation of the gonadotropic cells.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[7][8][9][10] Pharmacological stimulation of gonadotropins by GnRH also showed overlapping gonadotropin serum concentrations. 7,10,11 In contrast, pharmacological stimulation of gonadotropins by GnRH agonists (GnRHa) showed a significantly higher discriminatory potential. GnRH agonists have longer half-lives than GnRH and a stronger affinity for the GnRH receptor, causing a supraphysiological and sustained stimulation of the gonadotropic cells.…”
Section: Introductionmentioning
confidence: 92%
“…Current laboratory studies have examined basal or stimulated concentrations of gonadotropins and basal or stimulated testosterone concentrations, as well as basal inhibin B and AMH concentrations . Basal serum gonadotropin concentrations were shown to be poor discriminators except in one study . Pharmacological stimulation of gonadotropins by GnRH also showed overlapping gonadotropin serum concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned studies [7,8,9,10,11,12,13] as well as other studies [14, 15] were performed using radioimmunoassays with low sensitivity and a detection limit higher than prepubertal levels. The development of new assays with higher sensitivity has recently provided useful information on the regulation of gonadotropins in prepubertal children and offered improved diagnosis of many pubertal disorders [16,17,18,19,20]. In addition, these assays have demonstrated that normal prepubertal levels of LH and FSH are much lower than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…Grinspon et al 8 had shown a 100% diagnostic specificity of basal FSH <1.2 IU/L for IHH in boys with delayed puberty, but the study consisted of only a very small number with CDGP. Sequera et al 38 showed exclusion of severe IHH with LH >0.65 IU/L, but did not identify thresholds to differentiate between partial IHH and CDGP. Although lower basal gonadotrophin levels on average have been demonstrated in IHH compared with CDGP, there is substantial overlap between the groups 37.…”
Section: Clinical Assessment and Treatment Of Delayed Pubertymentioning
confidence: 97%